ChemInform Abstract: Practical Pd/C‐Catalyzed Suzuki—Miyaura Reactions for the Preparation of 3‐Aryl‐4‐oxypyridin‐2(1H)‐ones, 3‐Aryl‐2, 4‐oxypyridines and 3‐Aryl‐2, 4‐oxyquinolines as Useful Intermediates for the Synthesis of Biologically Active Compounds. Issue 12 (14th March 2013) - Lamblin, Marc; Bares, Hugo; Dessolin, Jean; Marty, Christel; Bourgougnon, Nathalie; Felpin, Francoise‐Xavier
Abstract The reaction products can be further transformed into antiviral nucleosides.